Physical Characteristic and Palatability of Market Vegetable Waste Wafer for Sheep - Retnani, Y; Syananta, FP; Herawati, L; Widiarti, W; Saenab, A (ANIMAL PRODUCTION, 2010)
Vegetable waste is a part of vegetables or vegetables that are discarded. This vegetable market wastes are perishable, voluminous (bulky) and the availability was fluctuated so the processing technology is needed to make this vegetable waste become durable, easy to be stored and could be given to the animal. To solve this problem, vegetable waste could be formed into a wafer. The objective of this experiment was to determine the physical characteristic and palatability of vegetable market waste after formed into a wafer. The experimental design used in this research was Completely Randomized Design with 5 treatments and 4 replicates. The treatments were the composition of raw materials used: 100% corn husk  (R1); 75% corn husk  +25% mungbean waste (R2); 50% corn husk  + 25% mungbean waste + 25% cauliflower leaf  (R3); 25%  corn husk +50% mungbean waste + 25% cauliflower leaf  (R4); 25% corn husk  + 25% mungbean waste  +50%  cauliflower leaf (R5).  Variables measured were water activity, water absorption, density and palatability. The results of this research indicated that treatments significantly affected water activity (P<0.08) and wafer palatability (P<0.05). The highly significant difference in water absorption and wafer density (P<0.01) were found among treatments. Based on physical characteristic, R1 had the highest water absorption.  R5 had the lowest water activity, whereas R3 had the highest wafer density. Wafer of R4 was the most palatable for the experimental sheep compare to other treatments. (Animal Production 12(1): 29-33 (2010)Key Words : physical characteristic,  palatability, wafer and vegetable waste